PROTECTION OF FAMILY: AN ISLAMIC APPROACH - Nasir Mehmmod (Journal of Religion and Society, 2025)
The family is one of the basic building blocks of society, which consists of a group of families. The home is the primary source that provides the nation with men and women. If this primary source is good, pure, free from corruption, chaos, and strife, and characterized by cooperation, protection, prevention, and order, then its provision will be good for the nation and will increase the number of its righteous individuals who become the foundations of strength and cooperation in its larger society. If this source is tainted with corruption and built on selfishness, chaos, and neglect, then its provision will be evil for the nation and a danger to its society. This is what Allah the Almighty referred to when He said: {And the good land - its vegetation emerges by permission of its Lord. But that which is bad - nothing emerges except with difficulty.} [Al-A'raf: 58].One of the objectives of Islamic law is the interest of the family and its protection, which is the foundation of human society and from which nations are composed. Therefore, the law paid great attention to it and built it on strong foundations of affection, justice, and other things. It provided many, many means to protect the family from corruption and disintegration.In our current era, many challenges have emerged and various and diverse problems have appeared as a result of technological progress and globalization, which had profound effects on the family first and society second. These matters have destroyed the family system in the West and are gradually moving towards Islamic countries. The reason for this is actually due to not following the law and not taking appropriate measures to protect the family. Therefore, today we are in dire need to take steps to protect the family in light of the manifestations and means of Sharia. This research attempts to answer the questions: What is the importance of the family in Islam? What are its objectives? What are the legal means and manifestations to protect the family in the face of contemporary challenges that cause family disintegration? Keywords: Building, Society, Protection, Prevention, Contemporary, Manifestations Disintegration.